2002
DOI: 10.1124/dmd.30.11.1288
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stereochemistry of the Active Metabolite of Clopidogrel

Abstract: ABSTRACT:Clopidogrel (SR25990C, PLAVIX) is a potent antiplatelet drug, which has been recently launched and is indicated for the prevention of vascular thrombotic events in patients at risk. Clopidogrel is inactive in vitro, and a hepatic biotransformation is necessary to express the full antiaggregating activity of the drug. Moreover, 2-oxo-clopidogrel has been previously suggested to be the essential key intermediate metabolite from which the active metabolite is formed. In the present paper, we give the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
337
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 419 publications
(355 citation statements)
references
References 11 publications
9
337
1
8
Order By: Relevance
“…Clopidogrel [SR25990C, 2-(2-chlorophenyl)-2-(2,4,5,6,7,7a hexahydrothieno [3,2c] pyridine-5yl-acetic acid methyl ester hydrogen sulfate 7S] was from Sanofi-Aventis (Toulouse, France). The active metabolite of clopidogrel (ActMet) was obtained by biotransformation and purified as described (54,55).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clopidogrel [SR25990C, 2-(2-chlorophenyl)-2-(2,4,5,6,7,7a hexahydrothieno [3,2c] pyridine-5yl-acetic acid methyl ester hydrogen sulfate 7S] was from Sanofi-Aventis (Toulouse, France). The active metabolite of clopidogrel (ActMet) was obtained by biotransformation and purified as described (54,55).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in vivo studies have demonstrated that clopidogrel has to undergo hepatic metabolization to obtain an active metabolite (53). This active metabolite (Act-Met) has been isolated, and its structure has been elucidated (54). It contains a free thiol function, and its activity is lost when the thiol is derivatized (55), suggesting its possible interaction with cysteine-containing sequences.…”
mentioning
confidence: 99%
“…The active metabolite of clopidogrel [molecular weight (MW) 353 Da] has low-BBB permeability (24). Clopidogrel would thus not be expected to interfere with the movement of microglia or their ramified processes under control conditions.…”
Section: Systemic Clopidogrel Suppresses Juxtavascular Microglial Celmentioning
confidence: 99%
“…More importantly, the efficacy enhancement is unlikely to jeopardize the clinical safety records of CPG. Currently, to overcome the disadvantages of CPG, substituting therapies are as follows: (1) dose increase of CPG (e.g., doubling), (2) adjunctive use of cilostazol with CPG, and (3) use of other antiplatelet agents, such as prasugrel or ticagrelor. 21 Being closely related to CPG, the improved deuterated analogues are expected to stay in the narrow therapeutic window and be potentially more beneficial than the above alternative treatments.…”
Section: * S Supporting Informationmentioning
confidence: 99%